The seed biochemical composition and the genetic diversity of some local upland rice cultivars collected from Caobang and Backan provinces - Mau, Chu Hoang; Thu Nga, Pham Thi (Academia Journal of Biology, 2014)
The local upland rice cultivars play an important role for the life of people in upland regions of North Vietnam. The quantity of local upland rice cultivars has been degenerated considerably by the adverse environment conditions and the development of agricultural and sylvicultural productions. So that, the preservation of the gene source of local upland rice cultivars are very necessary. 18 local upland rice cultivars had been collected from the Caobang and Backan provinces. They belonged to two rice subspecies indica (13 cultivars) and japonica (5 cultivars) and consisted of 7 sticky rice cultivars and 11 plain rice cultivars. The agro-biological characters and the seed quality of these local upland rice cultivars had been assessed. The total protein content of their seeds ranged from 4.83% to 8.91% and the total lipid content ranged from 1.82% to 3.91% of dry weight. The molecular genetic diversity of some local upland rice cultivars had been analyzed by RAPD markers with 5 arbitrary primers and the result obtained showed that 285 fragments have been replicated. The significal difference between these local upland rice cultivars were shown by the study of the DNA polymorphism at molecular level and the appearance of 2 plant groups with difference from 11.6% to 48.5% has been compared with the similar coefficient of local upland rice cultivars.